Abortion round the world - Brown, Hannah (BMJ Publishing Group Ltd., 2007)
In the recent UK debates about the upper time limit for termination of pregnancy, attention focused on the number of abortions since legalisation. But, as Hannah Brown reports, rates of abortions have been falling faster in Western countries than elsewhere